2017
DOI: 10.1089/rej.2016.1855
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Its Association with Frailty Among Men Aged 80 Years or Older in Taiwan: A Cross-Sectional Study

Abstract: About one fifth of study subjects had UI (mostly urgency and functional incontinence type), which was significantly associated with frailty, stool incontinence and depressive symptoms. Further study is needed to evaluate the possibilities of reversing these geriatric syndromes by an integrated intervention program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
6
21
1
4
Order By: Relevance
“…A Brazilian cross-sectional urban study in an independent elderly population showed that incontinence doubled in the frail vs nonfrail (42.9% vs 20.8%, respectively). 62 Similarly, in a Taiwanese study from veterans' nursing homes, the presence of frailty was more common among people with urinary incontinence than those without (60.7% vs 32.3%, P <.001) 63 but, as in the Brazilian study, nocturnal LUTS were not expressed separately from overall incontinence.…”
Section: Nocturia In the Frail Elderlymentioning
confidence: 85%
“…A Brazilian cross-sectional urban study in an independent elderly population showed that incontinence doubled in the frail vs nonfrail (42.9% vs 20.8%, respectively). 62 Similarly, in a Taiwanese study from veterans' nursing homes, the presence of frailty was more common among people with urinary incontinence than those without (60.7% vs 32.3%, P <.001) 63 but, as in the Brazilian study, nocturnal LUTS were not expressed separately from overall incontinence.…”
Section: Nocturia In the Frail Elderlymentioning
confidence: 85%
“…Polypharmacy was defined as the use of more than four medications, and a systemic review has clearly established a strong relationship between polypharmacy and negative clinical consequences . Other variables including history of dementia, visual/hearing impairment, history of fall in the recent 1 year, urinary incontinence and the use of antipsychotic drugs have been previously described in detail …”
Section: Methodsmentioning
confidence: 94%
“…27 Other variables including history of dementia, visual/hearing impairment, history of fall in the recent 1 year, urinary incontinence and the use of antipsychotic drugs have been previously described in detail. 28…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 99%
“…Do mesmo modo, foi observada em estudo com 440 idosos institucionalizados (≥80 anos), de quatro cidades de Taiwan. Os resultados apontaram prevalência de 19,1% (n=84) idosos com IU, inferior ao presente estudo, ainda assim houve associação significativa entre fragilidade física e IU (p<0,001) (20) .…”
Section: Discussionunclassified